Effect of non-vital tooth bleaching photoactivated with blue or violet LED on color and microhardness - Almeida, Eran Nair Mesquita de [UNESP]; Costa, Joatan Lucas de Sousa Gomes [UNESP]; Besegato, Joao Felipe; Silva, Aryvelto Miranda; Manzoli, Tatiane Miranda [UNESP]; Vitoria, Matheus Sousa [UNESP]; Andrade, Marcelo Ferrarezi de [UNESP]; Kuga, Milton Carlos [UNESP] (Elsevier B.V., 2023)
Background: To evaluate the efficacy of dental bleaching protocols using 35% hydrogen peroxide photoactivated with violet LED on color and microhardness of endodontically treated teeth. Methods: Forty specimens were selected and randomized into 4 groups (n = 10): C -Control, HP -35% hydrogen peroxide, HP + BL -35% hydrogen peroxide + blue LED, HP + VL -35% hydrogen peroxide + violet LED. Three bleaching sessions were performed for each group. Color analysis was performed 7 days after each bleaching session. Two-way repeated measure ANOVA and Bonferroni test were used to evaluate the effect of different bleaching protocols and evaluation times on the dependent variables (Delta E and Delta L). Dentin microhardness was measured 24 h after the third bleaching session. Data were evaluated by ANOVA and Tukey's test at a signifi-cance level of 5%. Results: Differences on Delta E and Delta L were verified after the first and second bleaching sessions (p < 0.05) and showed stability after the third one, for all the groups. No differences were observed among HP, HP + BL, and HP + VL groups, regardless of the evaluation time (p > 0.05). HP and C showed the greatest and smallest reduction in dentin microhardness (p < 0.05), respectively. No difference between HP + BL and HP + VL pro-tocols (P > 0.05) was observed. Conclusions: High concentration hydrogen peroxide (35%) photoactivated with violet LED bleached endodonti-cally treated teeth effectively. However, the same protocol negatively affected the dentin microhardness, but not in the same level of 35% HP solely used.
Keywords: Endodontics; Dental bleaching; Hydrogen peroxide; LED; Microhardness; violet